2016
DOI: 10.1016/j.concog.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between different types of dissociation and psychosis-like experiences in a non-clinical sample

Abstract: This study investigates whether detachment-type dissociation, compartmentalisation-type dissociation or absorption was most strongly associated with psychosis-like experiences in the general population. Healthy participants (N=215) were tested with the Dissociative Experiences Scale (DES, for detachment-related dissociative experiences); the Harvard Group Scale of Hypnotic Susceptibility (HGSHS:A, for dissociative compartmentalisation);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…This finding is consistent with other studies that have reported an association between absorption, hallucinatory experiences and ASEs (Glicksohn & Barrett, 2003; Humpston et al, 2016; Perona-Garcelan et al, 2012). …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding is consistent with other studies that have reported an association between absorption, hallucinatory experiences and ASEs (Glicksohn & Barrett, 2003; Humpston et al, 2016; Perona-Garcelan et al, 2012). …”
Section: Discussionsupporting
confidence: 93%
“…Importantly, however, some bipolar and non-clinical participants were also categorized as members of this cluster, suggesting that absorption may be an important dimension of psychosis (or psychotic like experiences) understood not as a categorical construct but a dimensional population level continuum. This finding aligns with prior research finding elevated absorption scores among healthy adults with psychotic-like experiences (Humpston et al, 2016). …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with these longitudinal observations, experimental evidence suggests that sleep deprivation has a causal effect on PLEs. For instance, Giesbrecht and colleagues showed that one night of sleep deprivation increased dissociative experiences that share many features with PLEs . Further studies have shown that total sleep deprivation induced PLEs , but the mediating role of negative affect following experimental sleep deprivation remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%